2011
DOI: 10.4103/2006-8808.78470
|View full text |Cite
|
Sign up to set email alerts
|

Penile gangrene: An unusual complication of priapism in a patient with bladder carcinoma

Abstract: A 40-year-old, apparently healthy farmer presented with a 4-day history of progressively painful penile erection with no known predisposing or precipitating factor. He had an emergency El-Ghorab shunt which resulted in almost complete detumescence. He was noticed to have developed ischemic changes of the distal part of the penile skin which progressed to gangrene of the distal part of the penis on the 4th day post intervention. Abdomino-pelvic ultrasound revealed an intravesical mass and urine and corpus caver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…This condition is associated with priapism, intense external pressure on the penis (clothing, suction devices), Wegener's granulomatosis, septic emboli in IV drug users, perivascular invasion of the penis by a tumour, penile surgery, and, most commonly, diabetes mellitus (DM) [11–15]. Several factors can act simultaneously causing gangrene of the penis.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is associated with priapism, intense external pressure on the penis (clothing, suction devices), Wegener's granulomatosis, septic emboli in IV drug users, perivascular invasion of the penis by a tumour, penile surgery, and, most commonly, diabetes mellitus (DM) [11–15]. Several factors can act simultaneously causing gangrene of the penis.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic priapism is usually associated with many concomitant diseases and risk factors, such as hematological, traumatic, surgical, neoplastic, neurological, infective and pharmacological factors. Numerous studies 7,8 have indicated that leukemia and malignant tumors are associated with priapism, and several psychotropic drugs have also been reported to cause priapism as a side effect. 9,10 In our series, seven patients had primary diseases, and the other two denied obvious precipitating factors, including three with CML, two with a malignant tumor, one with infection and one with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology were idiopathic (6/14), sickle cell disease (5/14), traumatic (1/14), urethral carcinoma (1/14) and unknown in one patient. The other two cases reported in the literature were as a result of thrombotic thrombocytopenic purpura3 and the other due to metastasis into the penis from a primary bladder malignancy 4. All patients had undergone intervention to relieve priapism in the form of aspiration and irrigation or creation of distal shunt prior to development of gangrene.…”
Section: Discussionmentioning
confidence: 99%